A Hollow Multi‐Shelled Structure for Charge Transport and Active Sites in Lithium‐Ion Capacitors. Issue 12 (29th January 2020) - Bi, Ruyi; Xu, Nan; Ren, Hao; Yang, Nailiang; Sun, Yonggang; Cao, Anmin; Yu, Ranbo; Wang, Dan
Abstract: The lithium‐ion capacitor (LIC) has attracted tremendous research interest because it meets both the requirement on high energy and power densities. The balance between effective surface areas and mass transport is highly desired to fabricate the optimized electrode material for LIC. Now, triple‐shelled (3S) Nb2 O5 hollow multi‐shelled structures (HoMSs) were synthesized for the first time through the sequential templating approach and then applied for the anode of LIC. The unique structure of HoMSs, such as large efficient surface area, hierarchical pores, and multiple shells, provides abundant reaction sites, decreases the electron transport resistance, and increases the diffusion rate for ion transport. In this case, the best combination performance has been achieved among all the reported Nb2 O5 ‐based materials, which delivered an excellent energy and power densities simultaneously, and superb cycling stability. Abstract : Live LICs : The balance of active sites and charge transport allow Nb2 O5 with a hollow multi‐shelled structure to deliver excellent energy density, an ultrahigh power density, and good cycle stability for high‐performance Li‐ion capacitors (LICs).